Formulasi dan Karakterisasi Larutan Irigasi Berbasis Ekstrak Buah Lerak (Sapindus rarak DC.) - Maria Indriati ose; Sizka Irdianti; Perdiansyah Perdiansyah; Neng Nely Widiyanti Rahma; Syifa Aulia Putri; Cesarianti Dwi Puteri Hatmoko; Feronika Evma Rahayu (STIKes Medistra Indonesia, 2026)
The lerak fruit (Sapindus rarak DC.) is a plant that contains high levels of saponins (20–28% of dry weight) and can be developed as a natural active ingredient in solution form for wound care due to its surfactant properties and ability to inhibit microbial growth. This study aims to formulate and characterize irrigation solutions using a 25% lerak fruit extract in three different formulations: F1, consisting of the extract, sodium chloride, activated carbon, and a solvent; F2, consisting of the extract, activated carbon, and a solvent; and F3, consisting only of the extract and a solvent. Physical quality evaluation included organoleptic testing, clarity, pH, displaced volume, leakage, foam height, and specific gravity, in accordance with the provisions of the Indonesian Pharmacopoeia, 6th Edition. The results showed that all three formulations had the same sensory characteristics (reddish-brown color, distinctive aroma, liquid form), a displacement volume of 100%, and no signs of leakage. Clarity tests showed that all three formulations appeared clear but still contained submicron colloidal particles due to the presence of saponin micelles and tannin-protein aggregates. The pH values of the three formulations (F1=3.75; F2=3.84; F3=3.77) were below the normal pH range of healthy skin (4.5–5.5), so pH adjustment is necessary. Foam content tests showed good foaming ability in all formulations (F1 = 78.33%; F2 = 76.33%; F3 = 75.00%), which is related to the saponin content that acts as a natural surfactant. The specific gravity test showed that F1 had a density of 1.0084 g/mL and F2 had a density of 1.0088 g/mL, which are nearly identical to the density of water. However, F3 had a density of 0.7658 g/mL, which is significantly different and poses a risk of being hypotonic. This pattern is related to the presence of activated carbon in the formula. Overall, F1 exhibits the most balanced physical properties compared to the other three formulations. However, all formulations still require pH adjustment and further purification before they can be developed into candidate burn irrigation solutions derived from natural ingredients that possess good quality, stability, and safety.